Acquired interferon γ responsiveness during Caco-2 cell differentiation: effects on iNOS gene expression. Issue 5 (1st May 1999) - Chavez, A M; Morin, M J; Unno, N; Fink, M P; Hodin, R A
Abstract : BACKGROUND: Impairment of intestinal barrier function occurs under a variety of inflammatory conditions and is mediated at least in part by interferon γ (IFN-γ) induced nitric oxide (NO) production. Previous in vivo studies have shown that systemic lipopolysaccharide treatment caused an induction of the rat inducible nitric oxide synthase (iNOS) mRNA primarily in villus cells, rather than in undifferentiated crypt cells. AIMS: To examine iNOS induction by IFN-γ in vitro as a function of enterocyte differentiation. METHODS: Preconfluent and postconfluent Caco-2 cells were treated with IFN-γ in the presence or absence of various inhibitors. Northern analyses were performed to assess the magnitude of iNOS mRNA induction. IFN-γ receptor mRNA and protein levels were determined. RESULTS: iNOS mRNA induction by IFN-γ occurred at two hours and was not blocked by cycloheximide, indicating that it is an immediate early response. iNOS induction and nitrite/nitrate increases were inhibited by dexamethasone and pyrrolidine dithiocarbamate, supporting an important role for the NF-κB transcription factor in this process. The stimulated iNOS induction was seen almost exclusively under conditions of cellular differentiation—that is, in postconfluent Caco-2 cells. This increased IFN-γ responsiveness seen in postconfluent Caco-2 cells correlated with an increased expression of IFN-γ receptor, whereas T84 and HT-29 cells did not show any significant alterations in either iNOS induction or IFN-γ receptor levels as a function of postconfluent growth. CONCLUSIONS: With regard to iNOS mRNA induction, IFN-γ responsiveness is acquired during Caco-2 cell differentiation, perhaps related to an increase in the numbers of IFN-γ receptors.